PERMAINAN ULAR TANGGA UNTUK MEMBANGUN KARAKTER SISWA - M.M. Endang Susetyawati; Kristina Warniasih; Ika Ernawati (CV. Denasya Smart Publisher, 2025)
Education is not merely intended to make children intelligent, but it must also be able to shape their character. Character provides a strong foundation for children to grow into successful and happy individuals in the future. Teachers can develop innovative learning strategies to foster character building, one of which is through the use of games. This community service activity aims to build students’ character through the snakes and ladders game. The activity was carried out at SD Negeri Sonosewu, Kasihan, Bantul. Two types of snakes and ladders games were used, namely the banner version and the digital version, both of which were equipped with question cards. The question cards contained tasks related to mathematics, singing, and general knowledge. The implementation method of this community service program included observation, lectures, and practical activities using the snakes and ladders game. To measure the success of the program, students were asked to share their impressions and experiences during the game sessions. Through this approach, the snakes and ladders game proved to be an effective learning medium to build students’ character from an early age. Moreover, the implementation of this community service program is expected to bring valuable benefits to the students of SD Negeri Sonosewu, Kasihan, Bantul